UV‐induced degradation of high‐efficiency silicon PV modules with different cell architectures. (7th July 2022) - Sinha, Archana; Qian, Jiadong; Moffitt, Stephanie L.; Hurst, Katherine; Terwilliger, Kent; Miller, David C.; Schelhas, Laura T.; Hacke, Peter
Abstract: Degradation from ultraviolet (UV) radiation has become prevalent in the front of solar cells due to the introduction of UV‐transmitting encapsulants in photovoltaic (PV) module construction. Here, we examine UV‐induced degradation (UVID) in various commercial, unencapsulated crystalline silicon cell technologies, including bifacial silicon heterojunction (HJ), interdigitated back contact (IBC), passivated emitter and rear contact (PERC), and passivated emitter rear totally diffused (PERT) solar cells. We performed UV exposure tests using UVA‐340 fluorescent lamps at 1.24 W·m −2 (at 340 nm) and 45°C through 4.02 MJ·m −2 (2000 h). Our results showed that modern cell architectures are more vulnerable to UVID, leading to a significant power decrease (−3.6% on average; −11.8% maximum) compared with the conventional aluminum back surface field (Al‐BSF) cells (<−1% on average). The power degradation is largely caused by the decrease in short‐circuit current and open‐circuit voltage. A greater power decrease is observed in bifacial cells with rear‐side exposure compared with those with front‐side exposure, indicating that the rear side is more susceptible to UV damage. Secondary ion mass spectroscopy (SIMS) confirmed an increase in hydrogen concentration near the Si/passivation interface in HJ and IBC cells after UV exposure; the excess of hydrogen could result in hydrogen‐induced degradation and subsequently cause higher recombination losses. Additionally, surface oxidation and hot‐carrier damage were identified in PERT cells. Using a spectral‐based analysis, we obtained an acceleration factor of 5× between unpackaged cells (containing a silicon nitride antireflective coating on the front) in the UV test and an encapsulated module (with the front glass and encapsulant blocking 90% of the UV at 294 nm and 353 nm, respectively) in outdoor conditions. From the analytical calculations, we show that a UV‐blocking encapsulant can reduce UV transmission in the module by an additional factor of ~50. Abstract : The use of UV‐pass encapsulants in PV modules is becoming a popular option to capture ~1% light gain; however, this makes the cells more susceptible to ultraviolet‐induced degradation. In this study, modern crystalline‐silicon PV technologies including HJ, IBC, PERT, and PERC cells have shown greater power degradation when exposed to UV as compared with traditional Al‐BSF cells, which is attributed to greater sensitivity to increasing surface recombination velocity (limited front surface field) from UV damage.